2021
DOI: 10.4103/sjmms.sjmms_401_20
|View full text |Cite
|
Sign up to set email alerts
|

Standing and Walking Balance in Patients with Chronic Shoulder Pain

Abstract: Background: Patients with shoulder pain may have proprioceptive and balance deficits. However, studies on balance in patients with shoulder pain are scarce. Objective: This study aims to investigate if patients with chronic shoulder pain demonstrate deficits in standing and walking balance and to study the relationship between outcome measures of balance and age and body mass index (BMI). Materials and Methods: This case–control study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Individuals with chronic shoulder pain, balance was evaluated with the Romberg test, and mobility and walking balance were evaluated with the timed one-leg stance test. As a result of this study, no significant difference was observed between the groups (Alshami and Alrammah, 2021). In our study, parallel to this study, TUG values were found to be correlated with balance scores and pain level.…”
Section: Discussionsupporting
confidence: 77%
“…Individuals with chronic shoulder pain, balance was evaluated with the Romberg test, and mobility and walking balance were evaluated with the timed one-leg stance test. As a result of this study, no significant difference was observed between the groups (Alshami and Alrammah, 2021). In our study, parallel to this study, TUG values were found to be correlated with balance scores and pain level.…”
Section: Discussionsupporting
confidence: 77%
“…No statistically significant difference was found between the groups in the study. We believe using field balance assessment methods instead of an objective assessment method called BBS might have led to this result (34).…”
Section: Discussionmentioning
confidence: 95%